The Hillz - Henry Hathaway; Betty, Field; Beulah Bondi; Harry Carey; James Barton; Marjorie Main; Samuel S Hinds; John Wayne (USA Paramount Pictures, 1941)
Young Matt Masters, an Ozark Mountains moonshiner, hates the father he has never seen, who apparently deserted Matt's mother and left her to die. His obsession contributes to the hatred rampant in the mountains. However, the arrival of a stranger, Daniel Howitt, begins to positively affect the mountain people, who learn to shed their hatred under his gentle influence. Still, Matt does not quite trust Howitt.....
Young Matt Masters, an Ozark Mountains moonshiner, hates the father he has never seen, who apparently deserted Matt's mother and left her to die...
Stuart Anthony
Language(s): English, Turkish Subtitle(s): Turkish
Keywords: Drama